PEMIKIRAN 'ABD AL-QADIR ‘AUDAH TENTANG KALAM, SYARI'AH, QANUN, DAN KHAWARIJ - B. Syafuri; Abdullah Jarir (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
This article tries to explain several points of 'Audah 's thoughts on kalam, syari'ah, qanun, and khawarij. 'Abd al-Qadir 'Audah is categorized as a great reformer who has revolutionary-minded. Along with his friends succeed to resurrect the Islamic doctrines in Egyptian society through the religious purification movement by using the slogan 'returning to the Qur'an and Sunnah'. Besides as great 'ulama’, he also deserved well for his country by overthrowing Faraouk, the tyrant king of Egypt, through the revolutionary action of 1952 in Egypt. Hence, it is logic if he was well-known as a great ulama and a revolutionary reformer of the twentieth century.